Analisis Fitokimia Ekstrak Pelarut Kulit Akar Tumbuhan â€œAt Anonseâ€ (Annona reticulata L.) - Maria Kasilda Elu; Oktovianus Kasa; Maria Aprista Manikin; Noviana Mery Obenu; Eduardus Edi (Saintek Lahan Kering, 2023)
Medicinal plants are plants that can be used as medicine or medicinal ingredients to treat various diseases. One of the plants used as a medicinal plant is Annona reticulata L. This study aims to determine the content of secondary metabolites in the solvent extract of the root bark of the plant â€œAt Anonseâ€ (Annona reticulata L.). The stages of this research were sample preparation, extraction, and phytochemical analysis. Extraction was carried out by maceration using n-hexane, ethyl acetate, and methanol as solvents. Phytochemical analysis was carried out qualitatively based on changes in color, precipitate and foam. The results of the phytochemical analysis test showed that the groups of compounds contained in the root bark of the plant â€œAt Anonseâ€ were triterpenoids, tannins, flavonoids, phenolics, alkaloids and saponins.